Creating an effective and equitable legal carbon taxing regime for South Africa - Delport, Erik (Institute of Marine and Environmental Law, 2018)
Human accelerated climate change presents a worldwide threat. It is a problem that requires international as well as local solutions. Human accelerated climate change is induced by the release of so called greenhouse gasses (GHG's) as a result of human activity, most notably by converting fossil fuels into energy. GHG's include Carbon dioxide (CO₂), Methane (CH₄), Nitrous oxide (N2O), Hydrofluorocarbons (HFCs), Perfluorocarbons (PFCs), and Sulphur hexafluoride (SF₆). The most notable of these gasses is Carbon Dioxide (CO₂), this gas is released into the atmosphere in vast amounts and is primarily responsible for the human contribution to climate change. In recent years, Governments all over the world have begun implementing strategies in order to decrease the amount of GHG's released into the atmosphere. The South African Government set out a range of options in the National Climate Change Response White Paper that could be used to reduce GHG emissions. The specific option which forms the subject matter of this dissertation is referred to as the Carbon Tax. Stripped down to its bare essentials a Carbon Tax entails that producers of GHG emitting products would pay a tax that corresponds to the amount of CO₂ emitted in the production of that product, or the CO₂ equivalent of the product if it emits one of the other GHG's. This amount of money is then incorporated into the price of the product making those emission intensive products more expensive. Theoretically, this should result in a decline in the consumption of the product and/or cleaner methods to produce the product. The underlying idea is to change consumers' behaviour to promote environmental goals by reducing GHG emissions. Carbon Taxing falls under a category of regulation which is referred to as the 'incentive based approach to environmental regulation' with the incentive being financial or market based. Incentive based measures are used in environmental regulation where traditional command and control measures would be insufficient or where they could be supplemented. This paper will examine the proposed Carbon Taxing regime for South Africa. It will assess the proposed regime in terms of its effectiveness as an instrument to reduce GHG emissions. It will also assess the equitability of the regime by assessing how the tax will affect citizens in different income classes.